2015
DOI: 10.1016/j.cyto.2014.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Diallyl disulfide inhibits TNFα induced CCL2 release through MAPK/ERK and NF-Kappa-B signaling

Abstract: TNFα receptors are constitutively overexpressed in tumor cells, correlating to sustain elevated NFκB and monocyte chemotactic protein-1 (MCP-1/CCL2) expression. The elevation of CCL2 evokes aggressive forms of malignant tumors marked by tumor associated macrophage (TAM) recruitment, cell proliferation, invasion and angiogenesis. Previously, we have shown that the organo-sulfur compound diallyl disulfide (DADS) found in garlic (Allium sativum) attenuates TNFα induced CCL2 production in MDA-MB-231 cells. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 55 publications
0
40
0
Order By: Relevance
“…Tumor angiogenesis results in abnormally formed, tortuous, and poorly organized vessels that exhibit altered permeability [108,109]. Previous researches have confirmed that the aberrant activated TNF-α receptor signaling is associated with coordination of tumor angiogenesis and metastasis [110]. DADS can inhibit the CCL2 (CC chemokine-2) releasing induced by TNF-α to play an antiangiogenesis role in MDA-MB-231 cells.…”
Section: The Inhibition Of Angiogenesis By Dadsmentioning
confidence: 96%
“…Tumor angiogenesis results in abnormally formed, tortuous, and poorly organized vessels that exhibit altered permeability [108,109]. Previous researches have confirmed that the aberrant activated TNF-α receptor signaling is associated with coordination of tumor angiogenesis and metastasis [110]. DADS can inhibit the CCL2 (CC chemokine-2) releasing induced by TNF-α to play an antiangiogenesis role in MDA-MB-231 cells.…”
Section: The Inhibition Of Angiogenesis By Dadsmentioning
confidence: 96%
“…Cellular models have been utilized to delineate the mechanisms by which garlic constituents may inhibit breast cancer growth (15)(16)(17)(18)(19)(20). For example, DATS treatment inhibited DNA strand breaks induced by an environmental carcinogen (benzo-[a]pyrene) in a non-tumorigenic normal human mammary epi-thelial cell line (MCF-10A) (16).…”
mentioning
confidence: 99%
“…The analysis carried out by Bauer et al () indicated that in the TNF‐α MDA‐MB‐231 breast cancer cell line, the NFκB transcriptional activity and the components of the MAPK pathway of kinases and CCL2 increase. In addition, these researchers found that the influence of TNF‐α diallyl disulfide is silenced, which involves the NFκB and MAPK pathways of the kinases.…”
Section: Discussionmentioning
confidence: 99%
“…Bauer et al () suggest its potential use to control the expression of TNF‐α and its surface receptors. This analysis also seems to confirm the assumed hypothesis of the complex and mutually interacting influence of the individual components of signaling cascades on themselves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation